2008
DOI: 10.1889/1.3069559
|View full text |Cite
|
Sign up to set email alerts
|

P‐186: High Quality Patterned Retarder for Transflective LCDs

Abstract: A patterned retarder for a transflective LCD can be fabricated by photo polymerization of a liquid crystalline monomer. It is required for the retarder that pattern size is smaller than pixel size of a LCD and that retardation of the retarder is thermally stable against over 200°C. We have optimized liquid crystalline monomer and fabrication processes of the retarder to achieve high quality patterned retarder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Fast response time not only reduces the undesirable motionpicture image blur but also enables color-sequential liquidcrystal displays (LCDs) using RGB (red, green, blue) LED backlights. 1,2 The latter is particularly attractive because it eliminates spatial color filters which in turn triples the optical efficiency and resolution density. Higher optical efficiency leads to lower power consumption which implies to an energy saving and longer battery life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast response time not only reduces the undesirable motionpicture image blur but also enables color-sequential liquidcrystal displays (LCDs) using RGB (red, green, blue) LED backlights. 1,2 The latter is particularly attractive because it eliminates spatial color filters which in turn triples the optical efficiency and resolution density. Higher optical efficiency leads to lower power consumption which implies to an energy saving and longer battery life.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymer-stabilized blue-phase liquid crystal (BPLC) [13][14][15][16] is emerging with potential to become a nextgeneration display because it exhibits the following revolutionary features: (1) submillisecond gray-to-gray response time, 17 (2) no need for surface alignment layer, (3) wide and symmetric viewing angle, and (4) cell-gap insensitivity provided that an in-plane-switching (IPS) electrode is employed. 18 The operation mechanism of a polymer-stabilized blue-phase liquid-crystal display (BPLCD) is drastically different from conventional nematic LCDs; the former is based on the Kerr-effect-induced isotropic-to-anisotropic transition 19 while the latter relies on the anisotropic-to-anisotropic LC director reorientation.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerizable liquid crystal (PLC) has been demonstrated a superior candidate for quarter wavelength retarder fabrication [14]. With sulfonic-dye-1 (SD1) as PLC photoalignment material, high-resolution micro-retarder array can be formed on top of a 45 • laminated linear polarizing film.…”
Section: B Fabricationmentioning
confidence: 99%
“…FSC-LCDs date back to 1982 when Clark and Shanks reported an FSC-LCD by combing a monochrome CRT with a two-frequency TN cell together with color polarizers, 1 and Bos et al reported an FSC-LCD by combing a monochrome CRT with a π-cell together with a color polarizer. 2 Later, in 1985, Hasebe and Kobayashi reported a flat-paneltype FSC-LCD using a narrow-gap TN-LCD (NTN-LCD) and a ferroelectric LCD (FLCD) together with color CRT tubes connected by a bundle of optical fibes, 3 and then Tanaka et al reported an FPD-type FSC-LCD using a narrow-gap TN-LCD and an FLCD together with an LED backlight. 4 Recently, several papers were presented on the reduction of color break-up and power reduction.…”
Section: Introductionmentioning
confidence: 99%